COMMUNICATIVE APPROACH IN ENGLISH LANGUAGE TEACHING (Лучшие интеллектуальные исследования, 2025)
Abstract: Today, communities are increasingly facing rapid and profound changes and tensions that affect the social, economic, and political aspects of life. The role of education has also become questionable in the millennial era. A matter of fact, 21 century education requires a gradual shift in curriculum construction focusing on the transferable competencies that learners need to develop in instructional settings. In today's knowledge-based, types of skills and competencies that students need to gain are different from in the past. Emphasizing the communicative competence is one of the most influential developments in language education. The implementation of communicative activities in EFL/ESL classroom prepares learners to use English in the world beyond based on their own needs, interests and opportunities.